2018
DOI: 10.1177/1758573218779078
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical testing of trans-humeral all-suture anchors for rotator cuff repair

Abstract: Background: Rotator cuff tears are one of the most common causes of shoulder pain. All-suture anchors are increasingly being used in the arthroscopic repair of rotator cuff tears. The purpose of this experimental study is to evaluate the biomechanical properties of all-suture anchors at different insertion sites in the proximal humerus relevant to rotator cuff repairs and the remplissage procedure. Methods: Sixteen cadaveric shoulders were used for the study. Four all-suture anchors were inserted in each proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…In conclusion, considering the benefits of arthroscopic tenodesis and the good biomechanical results with all suture anchor fixation, 14 we believe that our technique is a reproducible, simple, fast, and with many technical advantages ( Table 1 ). In addition, it is an alternative to be used in associated pathologies of the shoulder such as rotator cuff injuries.…”
Section: Discussionmentioning
confidence: 79%
“…In conclusion, considering the benefits of arthroscopic tenodesis and the good biomechanical results with all suture anchor fixation, 14 we believe that our technique is a reproducible, simple, fast, and with many technical advantages ( Table 1 ). In addition, it is an alternative to be used in associated pathologies of the shoulder such as rotator cuff injuries.…”
Section: Discussionmentioning
confidence: 79%
“…14,16-18 However, some notable exceptions can be found in the literature. Nagra et al 19 found the loads to failure of 4 ASAs, including 3 of the aforementioned anchors, to all be less than 150 N. In a study by Aramberri-Gutiérrez et al 20 on the 2.3-mm Iconix, loads were similarly low, between 150 and 225 N. Many studies directly compared ASAs with non-ASA anchors. Compared with metallic and bioresorbable anchors, ASAs tend to have higher loads to failure, though not always significantly so.…”
Section: Biomechanical Evidencementioning
confidence: 99%
“…12 In biomechanical studies, displacement after cyclic loading is used a surrogate measure. A handful of studies report displacements less than 2.5 mm for the 2.3-mm Iconix, 14,18,20 2.8-mm Y-Knot, 14,17,20 and 2.8-mm Q-Fix, 14 although some studies report displacements over 5 mm and as high as 15 mm. 16,19,21 However, in these studies with higher displacements, the displacements for ASAs are not significantly different than those of solid anchor controls.…”
Section: Biomechanical Evidencementioning
confidence: 99%